Mutants in orthophosphate-regulated cyclic phosphodiesterase showing rhythmic condiation in Neurospora - K. Hasunuma (Fungal Genetics Reports, 1985)
Mutants in orthophosphate-regulated cyclic phosphodiesterase showing rhythmic conidiation in Neurospora